Antihistamines in the treatment of pruritus in psoriasis - Domagała, Anna; Szepietowski, Jacek; Reich, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Aim : To evaluate the efficacy of antihistamines in reducing pruritus in psoriasis, 61 patients were randomized to be treated for 1 week with clemastine (n = 20), levocetirizine (n = 21) or placebo (n = 20). Material and methods : All patients received the same routine antipsoriatic treatment. Itch intensity was assessed with VAS and the Itch Questionnaire, and hand movements during sleep were counted with an accelerometer. Results : There was a statistically significant decrease in mean VAS scoring in clemastine and levocetirizine groups (p < 0.001), but not in the placebo group. Questionnaire scoring decreased significantly during the study in all study groups, with the greatest improvement noted in the clemastine group. The number of wrist movements during sleep did not differ significantly between groups. Conclusions : Antihistamines of the first and second generations seem to be effective in reducing itch in patients with psoriasis, albeit the antipruritic effect is rather moderate. These observations need to be confirmed on larger patient groups.